Sleep duration among patients with heart failure (HF) - Hesti Platini; Urip Rahayu; Leni Handayani (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2021)
Background: Heart disease or cardiovascular and blood vessel disease is one of the major health problems in developed and developing countries. One of the cardiovascular diseases is heart failure. Heart failure is the last stage of heart disease. The research regarding the description of demographic characteristics has a few, and necessary to conduct a study on this matter.Purpose: To describe the demographic characteristics and Sleep duration among patients with heart failure (HF) who were hospitalizationMethod: A quantitative descriptive research design, the sample taken by non-probability and purposive sampling. The number of samples of 62 participants. With criteria inclusion, patients with a diagnosis of right heart failure, functional classification New York Heart Association (NYHA) grades III and IV.Results: The most of the patient with heart failure by a mean age of 57. 32 old and standard deviation of 5.66 old, male (62.9%), the highest level of education was junior high school (58.1%) and sleep duration in range 2-10 hours by a mean of 4.53 hours and standard deviation of 2.3 hours. Accompanying disease by hypertension of 46.9%, use of sleeping pills ≥ 3 times a week 74.2%.Conclusion: The most patient has a sleep duration under 5 hours in 24 hours and use of sleeping pills ≥ 3 times a week. The management of heart failure to get the quality of life patients is getting better, considering that this disease is the final stage of heart disease. Good self-management compliance of sleep and rest needs through factors modifiable.